Preclinical Research to Clinical Practice: A Review of Phytochemicals in Cancer Treatment (International Journal of Innovative Research in Engineering & Management, 2022)
Cancer is a serious health issue that  remains a top cause of mortality across the globe.  Anticancer medications have been developed as we have  understood the molecular mechanism that leads to cancer  genesis has grown. Chemically produced medications, on  the other hand, have had little impact on overall survival  rates during the last several decades. As a result, to  improve the efficacy of conventional therapies of cancer,  new approaches and revolutionary chemoprevention  drugs are necessary. Phytochemicals are those molecules  that occur naturally in plants, are important resources for  developing new medicines and may also be used to treat  cancer. Only a few example include taxol analogues,  vinca alkaloids such as vinblastine vincristine and, and  podophyllotoxin analogues. These phytochemical generally work by interfering with  molecular pathways connected to cancer formation and  progress. Some of the distinct approaches include  increased antioxidants status, carcinogen inactivation,  reducing its rapid growth, promotion of cell cycle arrest  and death, and immune system regulation. The main goal  of this study is to summarise what we now know about  natural product active chemicals, including their  pharmacology and molecular or particular targets. The  most recent advancements and limitations in the  development of phytochemical-based anticancer therapies are also discussed. The author wants to boost  phytochemicals research not just for its scientific worth,  but also for its medicine development potential. As a  result, anticancer phytochemicals that have been studied  in preclinical and clinical settings have gotten a lot of  attention.
Keywords: Anticancer; Clinical; Medicinal Plants; Phytochemicals; Preclinical